ChemInform Abstract: Umpolung Synthesis of Diarylmethylamines via Palladium‐Catalyzed Arylation of N‐Benzyl Aldimines. Issue 43 (7th October 2016) - Li, Minyan; Yucel, Baris; Jimenez, Jacqueline; Rotella, Madeline; Fu, Yue; Walsh, Patrick J.
Abstract: The arylation of unsymmetrical aldimines (IV) and (VI) proceeds regioselectively at the sterically less hindered position leading to imines (V) and (VII), whilst the reaction of aldimine (VIII) affords a mixture of isomers (IX) and (X).